2021
DOI: 10.48550/arxiv.2109.14937
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Shadows and precession of orbits in rotating Janis-Newman-Winicour spacetime

Divyesh N. Solanki,
Parth Bambhaniya,
Dipanjan Dey
et al.

Abstract: In this paper, we construct the rotating Janis-Newman-Winicour (JNW) naked singularity spacetime using Newman-Janis Algorithm (NJA). We analyse NJA with and without complexification methods and find that the energy conditions do satisfied when we skip the complexification step. We study the shadows cast by rotating JNW naked singularity and compare them with the shadows cast by the Kerr black hole. We find that the shadow of the rotating naked singularity can be distinguished from the shadow of the Kerr black … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 55 publications
0
6
0
Order By: Relevance
“…Due to this property, the shape of the capturecross-section by light is transformed into an asymmetric one. An interesting astrophysical phenomenon is that the shadow of a rotating black hole has the asymmetric bright side due to this property [43,44,45,46,47,48,49,50,51,52,53,54].…”
Section: Energy Extraction From a Rotating Black Holementioning
confidence: 99%
“…Due to this property, the shape of the capturecross-section by light is transformed into an asymmetric one. An interesting astrophysical phenomenon is that the shadow of a rotating black hole has the asymmetric bright side due to this property [43,44,45,46,47,48,49,50,51,52,53,54].…”
Section: Energy Extraction From a Rotating Black Holementioning
confidence: 99%
“…One might come across abundant research literature concerning the aim to distinguish a naked singularity spacetime from any other spacetime which is engulfed by a null hypersurface or an event horizon. To distinguish these naked singularities, the significant work has been done in the recent literature [9][10][11][12][13][14][15][16][17], where authors investigate the shadows and orbital precession properties. Similarly, in this paper, we obtain an orbit equation of a test particle for the null-like naked singularity spacetime and we show the periastron precession of the timelike bound orbits for the same.…”
Section: Introductionmentioning
confidence: 99%
“…For this reason, many researchers have investigated observational signatures of the F/JNWW spacetime, e.g., gravitational lensing [14], the observable images of shadows and thin accretion disks [15,16], and the behavior of circular geodesics and the properties of accretion disks [17]. In particular, recent studies have shown that a naked singularity can exhibit a negative periapsis precession [18][19][20][21][22]. The negative periapsis precession is that the periapsis precessions in the direction opposite to the direction of a particle motion.…”
Section: Introductionmentioning
confidence: 99%
“…In [19][20][21], the authors have investigated the periapsis precession of orbits with small eccentricity in the weak field approximation in the F/JNWW spacetime. Furthermore, in [22], the authors numerically calculated and showed that the periapsis precession can take a negative value in the rotating F/JNWW spacetime. In this paper, we revisit the results in [20], where the authors focus on orbits with large semi-latus and small eccentricity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation